Drug Related Problems in Radio and Nuclear Pharmacy - Patel, Jyoti P.; Bhatt, Sandip P.; Sinha, Omprakash (Indian Journal of Pharmacy Practice)
Background: Radiopharmaceutical plays a critical role in modern medicine primarily for the diagnostic purpose, but also for monitoring disease progression and response to treatment. Identification, resolution and prevention of medication related problems is a vital role of healthcare professionals Drug related problems are an important challenge that may affect morbidity and mortality, as well as the patient’s quality of life. The Drug Related Problems recorded by the pharmacists were found to be of clinical significance lends support to actively including clinical pharmacists in the therapeutic health care team. Method: Data was collected in data collection form using patient’s medication file. Patients visiting department of nuclear medicine Gujarat Cancer and Research Institute, Ahmedabad were recruited in study. Data was collected in data collection form By reviewing patient’s medication file. Result: Total 65 patient included in the study and 146 DRPs identified in 56 (15.47%) patients. The frequency of Drug Related Problem was 2.60 per patient. Most common problems came to know were logistic problem(35.38%), repetition of report (35.38%), Imagine problem (37.69%), patient identifying problem (27.69%), dose selection problem (24.62%), administration problem (87.69%) and vein identifying problem (12.31%). Conclusion: It is concluded that apart from general medicines, Drug Related Problems also presented in nuclear and Radio Pharmaceutical product. Moreover there is a need to develop specific classification system to identify the Drug Related Problems associated with radio and nuclear pharmacy.
Keywords: Nuclear Pharmacy; Pharmacist; Drug Related Problems; Radio Pharmacy.